Validity of a four-item questionnaire in French assessing attachment to meat - Sebo, Paul; Tudrej, Benoit; Bernard, Augustin; Delaunay, Bruno; Dupuy, Alexandra; Malavergne, Claire; Maisonneuve, Hubert (Frontiers in Medicine, 2024)
The 16-item Meat Attachment Questionnaire (MAQ-16) assesses emotional and cognitive attachment to meat across four dimensions: hedonism, affinity, entitlement, and dependence. Recently validated in French, we aimed to develop and validate a shorter, four-item version (MAQ f -4) to reduce participant burden.In this 2023 observational study in the Rhône-Alpes region, 919 primary care patients were invited to complete the French MAQ-16 (MAQ f -16). Classical test theory guided the development of the MAQ f -4, and Spearman's correlation coefficients assessed its correlation with the MAQ f -16 (dimension and overall scores). We also evaluated the diagnostic performance of the MAQ f -4 for identifying patients with high meat attachment (MAQ f -16 score > 60).Results: A total of 822 patients participated (65.3% women; median age = 52; participation rate = 89.5%). The MAQ f -4 showed strong correlations with the MAQ f -16 (rho = 0.83 for hedonism, 0.77 for affinity, 0.70 for entitlement, 0.79 for dependence, and 0.86 for the overall score, all p-values < 0.001). A score of 15 on the MAQ f -4 (sensitivity = 91%, NPV = 96%) effectively excluded patients with low meat attachment, while a score of 17 (specificity = 96%, PPV = 84%) accurately identified those with high attachment.The MAQ f -4 demonstrated strong correlation with the MAQ f -16 and accurately identified high attachment to meat. It may serve as a useful tool in research and clinical settings, though further validation is required before broad implementation in French primary care.